2011
DOI: 10.1099/mic.0.050336-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of Klebsiella pneumoniae rmpA in capsular polysaccharide synthesis and virulence revisited

Abstract: Klebsiella pneumoniae community-acquired pyogenic liver abscess (PLA) is an emerging infectious disease. The rmpA gene (for regulator of mucoid phenotype A) has been reported to be associated with PLA in prevalence studies. NTUH-K2044, a K1 PLA isolate, carries three rmpA/A2 genes: two large-plasmid-carried genes (p-rmpA and p-rmpA2) and one chromosomal gene (c-rmpA). In this study, we re-examined the role of rmpA/A2 in PLA pathogenesis to clarify the relationship of rmpA/A2 and capsular serotype to virulence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
178
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(189 citation statements)
references
References 43 publications
10
178
0
1
Order By: Relevance
“…For example, increased glucose concentrations result in the upregulation of capsule production though RmpA, while relatively high extracellular iron concentrations result in the downregulation of capsule production. In fact, 55 to 100% of HV K. pneumoniae strains express at least one copy of rmpA or rmpA2, compared to 7 to 20% of non-HV K. pneumoniae strains (47,214). These genes positively regulate the cps locus at the transcriptional level, resulting in the hypercapsule phenotype (202,(215)(216)(217).…”
Section: Capsulementioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased glucose concentrations result in the upregulation of capsule production though RmpA, while relatively high extracellular iron concentrations result in the downregulation of capsule production. In fact, 55 to 100% of HV K. pneumoniae strains express at least one copy of rmpA or rmpA2, compared to 7 to 20% of non-HV K. pneumoniae strains (47,214). These genes positively regulate the cps locus at the transcriptional level, resulting in the hypercapsule phenotype (202,(215)(216)(217).…”
Section: Capsulementioning
confidence: 99%
“…These genes positively regulate the cps locus at the transcriptional level, resulting in the hypercapsule phenotype (202,(215)(216)(217). However, not all of these genes must be upregulated or even present concurrently (214,216,218,219). Hypercapsule production can be triggered in the absence of rmpA or rmpA2 by chromosomal mucoviscosity-associated gene A (magA) (41).…”
Section: Capsulementioning
confidence: 99%
“…Genes that encode a number of virulence factors, including those that are responsible for the hypermucoviscous phenotype (RmpA) and the siderophores (SP) aerobactin and salmochelin, are located on a large, 200-to 220-kb virulence plasmid that is not present in most cKP strains (16)(17)(18). Since the hypermucoviscous phenotype (which is probably due to increased capsule production) (reviewed in reference 2) was the initial defining trait of hvKP strains, it has received significant attention as a virulence factor and, despite conflicting data (2,(19)(20)(21), likely contributes to the increased pathogenicity. Other studies have identified factors that contribute to the virulence of hvKP, but these factors or properties are often present in cKP strains.…”
mentioning
confidence: 99%
“…A distinguishing factor of many hvKP strains is its hypermucoviscous phenotype (14). This phenotype has been established to be due to increased capsular polysaccharide (e.g., K1, K2 et al) production (15)(16)(17). Although K1 and K2 capsular serotypes have been shown to contribute to the virulence of cKP strains in a mouse IP challenge model (18), increased expression of the K2 capsule (hypermucoviscous phenotype) has been shown to add to the virulence of hvKP in a mouse IP challenge model (15).…”
mentioning
confidence: 99%